Cardio-metabolic parameters are associated with genetic admixture estimates in a pediatric population from Colombia (2016)
ABSTRACT: There are different genetic patterns for cardio-metabolic parameters among different populations. Additionally, it has been found that ancestral genetic components (the proportion of Amerindian, European and African) in admixed Latin American populations influence an individual’s susceptibility to cardio-metabolic disorders. The aim of this study was to evaluate the effect of ancestral genetic composition on a series of cardio-metabolic risk factors in a young admixed population from Colombia. Results: In a sample of 853 Colombian youth, 10 to 18 years old, the mean European contribution was 66.6 % (range: 41–82 %), the mean African contribution was 14 % (range: 4–48 %), and the mean Amerindian contribution was 19.4 % (range: 10–35 %) using a panel of 40 autosomal ancestry-informative markers (AIMs). We assessed the degree of association between ancestral African, Amerindian and European genetic components and measures of body mass index, waist circumference, fasting glucose, fasting insulin, insulin resistance, triglycerides, high-density lipoprotein, and systolic and diastolic blood pressure. Two of the nine measures assessed presented a nominal significant association with ancestral components after adjusting for confounding variables: triglyceride levels were associated with the Amerindian component (OR = 1.06, 98.3 % CI = 1.01–1.11, P = 0.002) and systolic blood pressure was associated with the European component (OR = 0.93, 98.3 % CI = 0.87 to 0.99, P = 0.008) and the African component (OR = 1.07, CI = 1.01–1.14 P = 0.008), although it was not significant following a global Bonferroni correction. Additionally, insulin levels and insulin resistance showed associations with the African component. Conclusions: Our findings support the idea that an Amerindian ancestral component may act as a risk factor for high triglyceride levels. In addition, an African ancestral component confers a risk for high systolic blood pressure, and a European ancestry serves as a protective factor for this condition in a young admixed population from Colombia. However, these results should be confirmed in a larger population.